Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$f(x) = \frac{6}{x}\,\, \mathrm{at}\,\, a = -4 .$$

Assume that $f$ has a power series expansion. Do not show that $R_n(x) -> 0$

I took the derivatives of f(x): $$f(x) = 6/x$$ $$f'(x) = -6/x^2$$ $$ f''(x) = 12/x^3 $$ $$ f^{(3)}(x) = -36/x^4 $$ but I am unable to write out the series, please help! Thank you

share|improve this question
    
Does my answer help you, or do you still need assistance? –  000 Dec 5 '12 at 6:24
    
thanks for your comment, but i do need a little more assistance if you do not mind. The truth is that i do not quite understand how to apply the nth derivative into the series –  Jaden Q Dec 5 '12 at 6:46
    
No problem! I'll update my answer. :) –  000 Dec 5 '12 at 6:50
    
I accidentally forgot the factor of $6$. I've fixed the addendum. I hope this helps. –  000 Dec 5 '12 at 7:21

2 Answers 2

up vote 1 down vote accepted

For a function $f$, the definition of the Taylor Series of $f$ is: $$\text{Taylor}(f)=\sum_{n \ge 0}\frac{f^{(n)}(a)}{n!}(x-a)^n, $$ where $f^{(n)}$ indicates the $n$th derivative of $f$ with $f^{(0)}=f$.

The problem, then, reduces to the following: Is there an $n$th derivative of $f(x)=\frac{6}{x}$? (More aptly, since $6$ is a constant: Is there an $n$th derivative of $\frac{1}{x}$? If so, what is it?)

Let's do a table of values: $$ \begin{align} \frac{d}{dx}\frac{1}{x}&=-\frac{1}{x^2}\\ \frac{d^2}{dx^2}\frac{1}{x}&=2\frac{1}{x^3}\\ \frac{d^3}{dx^3}\frac{1}{x}&=-6\frac{1}{x^4}\\ &\ldots \end{align} $$ This pattern seems to suggest $$\frac{d^n}{dx^n}\frac{1}{x}=(-1)^{n}n!\frac{1}{x^{n+1}}.$$

Let's prove this via induction on $n$. The base case trivially true. Assume the induction hypothesis for $n=k$. $$ \begin{align} \frac{d^{k+1}}{dx^{k+1}}\frac{1}{x}&=\frac{d}{dx}\frac{d^k}{dx^k}\frac{1}{x}\\ &=\frac{d}{dx}(-1)^kk!\frac{1}{x^{k+1}}\\ &=(-1)^kk!(k+1)(-1)\frac{1}{x^{k+2}}\\ &=(-1)^{k+1}(k+1)!\frac{1}{x^{k+2}}. \end{align} $$

Thus, via induction, we see this is correct!

Can you take this from here? Apply the $n$th derivative and the definition of $\text{Taylor}(f)$.


Okay, so you have the following pieces of information: $a=-4$, $f^{(n)}(x)=(-1)^nn!\frac{1}{x^{n+1}}$, and the definition of the Taylor Series. You simply substitute these into the definition as follows:

$$ \text{Taylor}(f)=6\sum_{n \ge 0}\frac{(-1)^nn!\frac{1}{a^{n+1}}}{n!}(x-a)^n=6\sum_{n \ge 0}\frac{(-1)^nn!\frac{1}{(-4)^{n+1}}}{n!}(x-(-4))^n . . . $$

Try to go from here and simplify this. :)

share|improve this answer
    
thank you so much! –  Jaden Q Dec 5 '12 at 7:56
    
Thank you for the lovely question! :-) –  000 Dec 5 '12 at 8:01

Refer to the definition of Taylor Series. You will have to evaluate your derivatives at $a=-4$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.